Numerical analysis of the impact of non-contact fins on the natural convection during melting process - Zhicheng Zhang; Zuoqin Qian; Lumei Zhao; Qiang Wang; Baolin Wang (Case Studies in Thermal Engineering)
Adding fins is an effective method to accelerate melting proccess. However, fins may not necessarily reduce the melting time due to the negative effects for natural convection. This paper propossed non-contact fins to investigate the impact of fins on convection during the melting process. The results indicate that the melting time can be reduced by up to 10.1 % and increased by 11 % for non-contact fins through different mounting methods. Moreover, the weakening mechanism of the fins can be described as the local convection reduction caused by the narrow spacing between the fins, and the momentum loss resulting from the liquid impacting the fin surfaces. Moreover, the velocity in the mushy region and the normal velocity at the solid-liquid interface serve as more reliable evaluation indicators.